A Comparative Analysis of Rhetorical Structures in English L1 and L2 Undergraduate Dissertation Introductions - Pérez Ruiz, Leonor; Pizarro-Sánchez, Isabel (Miscelánea: A Journal of English and American Studies, 2025)
Undergraduate dissertations (UDs) are the final academic piece of work undertaken by undergraduate students and their purpose is to evaluate mastery of the skills acquired throughout the curriculum. They include an introduction that, among other rhetorical functions, sets the general style of the entire dissertation, presents the research context and objectives, and seeks to persuade the evaluation committee of its quality and, thus, its relevance in the academic context. Based on Swales’s model (1990, 2004) for the analysis of research article introductions, we examine the rhetorical structure of UD introductions written by native and non-native speakers of English to establish whether there are differences in the rhetorical structure and the order of its moves and steps. The data analysed were retrieved from a comparable corpus of 40 introductions. Results indicate that non-native English speakers write shorter introductions with fewer steps and with a more linear rhetorical structure than their counterparts, and both groups fail to state the value of their research. Findings indicate that students require additional guidance in the writing of this academic genre.